2014
DOI: 10.1007/s13277-014-1615-8
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 and BRCA1 mRNA expressions are associated with clinical outcome of non-small cell lung cancer treated with platinum-based chemotherapy

Abstract: We conducted a perspective study to investigate whether the expression of excision repair cross-complementing 1 (ERCC1), xeroderma pigmentosum group G (XPG), breast cancer 1 (BRCA1), and ribonucleotide reductase M1 (RRM1) is correlated with clinical outcome of non-small cell lung cancer (NSCLC). Patients with histologically confirmed inoperable stages IIIB and IV NSCLC were collected and followed up until January 2012. Relative cDNA quantification for ERCC1, XPG, BRCA1, and RRM1 was performed using a fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Qin et al [17] assessed 116 death cases involving NSCLC using BRCA1 IHC analysis of inoperable stages IIIB and IV and confirmed that patients with high protein expression of BRCA1 were correlated with shorter OS and PFS times, compared to patients with low BRCA1 expression levels. In the present study, survival analysis of 65 death cases of NSCLC demonstrated that patients with negative BRCA1 expression showed longer OS time compared with patients with positive BRCA1 expression (median OS: 34 vs. 21 months, P = 0.011), and their adjusted HRs (95 % CI) for OS were 1.913 (1.161-3.150), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Qin et al [17] assessed 116 death cases involving NSCLC using BRCA1 IHC analysis of inoperable stages IIIB and IV and confirmed that patients with high protein expression of BRCA1 were correlated with shorter OS and PFS times, compared to patients with low BRCA1 expression levels. In the present study, survival analysis of 65 death cases of NSCLC demonstrated that patients with negative BRCA1 expression showed longer OS time compared with patients with positive BRCA1 expression (median OS: 34 vs. 21 months, P = 0.011), and their adjusted HRs (95 % CI) for OS were 1.913 (1.161-3.150), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…ERCC1 has been widely used for predicting the sensitivity of platinum-based chemotherapy of NSCLC [22,23]. A study by Qin et al [22] also showed that high expression of BRCA1 was correlated with a shorter OS and progression free survival (PFS) compared to low expression.…”
Section: Resultsmentioning
confidence: 99%
“…ERCC1 has been widely used for predicting the sensitivity of platinum-based chemotherapy of NSCLC [22,23]. A study by Qin et al [22] also showed that high expression of BRCA1 was correlated with a shorter OS and progression free survival (PFS) compared to low expression. Lee et al [24] found that low TS expression was significantly associated with a better response rate (RR) (P=0.037) and a longer PFS (P<0.001) in patients with pulmonary adenocarcinoma who were treated with pemetrexed/cisplatin as first-line chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…About in vitro studies, resistance to platinum associated with the expression levels of ERCC1 mRNA in ovary (Steffensen et al, 2014), testis (Schettino et al, 2008), bladder and lung cancers (NSCLC) (Qin et al, 2014) were studied and the existence of this relationship in patients with chronic gastric, ovarian, colon, esophagus and NSCLC cancer were confirmed (Schettino et al, 2008).…”
Section: In Iranian Patients With Advanced Gastric Cancer Receiving Pmentioning
confidence: 99%